HUBUNGAN MANUSIA DAN SUNGAI BENGAWAN SOLO SEBAGAI SUMBER INSPIRASI PENCIPTAAN KARYA SENI GRAFIS - Ahmad, Faheem Tahir; PA, Albertus Rusputranto (Institut Seni Indoensia Surakarta, 2022)
The creation of this final project is based on knowledge about changes in human relations with rivers, especially the Bengawan Solo river, whose impact can now be felt by living things that live around the Bengawan Solo River and its tributaries. The purpose of this Final Project is to create a silk screen work that takes inspiration from changes in human relations and the Bengawan Solo river, which indirectly explains the concept of creation, the process of creation, and the aesthetics of the shape of the created silk screen work. The creation of this Final Project provides more insight into the tools, materials, and techniques of working on work. The results obtained from the creation of this Final Project are silkscreen and the deepening of the concept of changing human relations and the Bengawan Solo river, which is expected to be useful for writers and other people who appreciate the works of this Final Project.